Oral Contraceptives Attenuate Cardiac Autonomic Responses to Musical Auditory Stimulation: Pilot Study - Milan, Reveni Carmem [UNESP]; Plassa, Bruna de Oliveira [UNESP]; Guida, Heraldo L. [UNESP]; Abreu, Luiz Carlos de; Gomes, Rayana L. [UNESP]; Garner, David M.; Valenti, Vitor E. [UNESP] (Innovision Communications, 2015)
Context The literature presents contradictory results regarding the effects of contraceptives on cardiac autonomic regulation. Objective The research team aimed to evaluate the effects of musical auditory stimulation on cardiac autonomic regulation in women who use oral contraceptives. Design The research team designed a transversal observational pilot study. Setting The setting was the Centro de Estudos do Sistema Nervoso Autonomo (CESNA) in the Departamento de Fonoaudiologia at the Universidade Estadual Paulista (UNESP) in Marilia, SP, Brazil. Participants Participants were 22 healthy nonathletic and nonsedentary females, all nonsmokers and aged between 18 and 27 y. Interventions Participants were divided into 2 groups: (1) 12 women who were not taking oral contraceptives, the control group; and (2) 10 women who were taking oral contraceptives, the oral contraceptive group. In the first stage, a rest control, the women sat with their earphones turned off for 20 min. After that period, the participants were exposed to 20 min of classical baroque music (ie, Canon in D Major, Johann Pachelbel), at 63-84 dB. Outcome Measures Measurements of the equivalent sound levels were conducted in a soundproof room, and the intervals between consecutive heartbeats (R-R intervals) were recorded, with a sampling rate of 1000 Hz. For calculation of the linear indices, the research team used software to perform an analysis of heart rate variability (HRV). Linear indices of HRV were analyzed in the time domain: (1) the standard deviation of normal-to-normal R-R intervals (SDNN), (2) the root-mean square of differences between adjacent normal R-R intervals in a time interval (RMSSD), and (3) the percentage of adjacent R-R intervals with a difference of duration greater than 50 ms (pNN50). The study also analyzed the frequency domain low frequency (LF), high frequency (HF), and LF/HF ratio. Results For the control group, the musical auditory stimulation reduced (1) the SDNN from 52.2 +/- 10 ms to 48.4 +/- 16 ms (P = .0034); (2) the RMSSD from 45.8 +/- 22 ms to 41.2 +/- 19 ms (P = .0128); (3) the pNN50 from 25.5 +/- 19 to 22.0 +/- 18 (P = .0211); and (4) the LF (ms(2)) from 954.8 +/- 457 ms(2) to 686.2 +/- 491 ms(2) (P = .0024). In the oral contraceptive group, no significant changes occurred for the HRV indices during exposure to music. Conclusions Musical auditory stimulation had a greater influence on cardiac autonomic regulation in women who did not use oral contraceptives.